Germination Protein Levels and Rates of Germination of Spores of Bacillus subtilis with Overexpressed or Deleted Genes Encoding Germination Proteins - Stewart, Kerry-Ann V. (American Society for Microbiology, 2012)
Deletion of Bacillus subtilis spores' GerA germinant receptor (GR) had no effect on spore germination via the GerB plus GerK GRs, and loss of GerB plus GerK did not affect germination via GerA. Loss of one or two GRs also did not affect levels of GRs that were not deleted. Overexpression of GRs 5- to 18-fold increased rates of germination via the overexpressed GR and slowed germination by other GRs up to 15-fold. However, overexpression of one or two GRs had no effect on levels of GRs that were not overexpressed. These results suggest that either interaction between different GRs reduces the activity of GRs in triggering spore germination or all GRs compete for interaction with a limiting amount of a downstream signaling molecule in the germination pathway. Overexpression or deletion of GRs also had no effect on spores' levels of the GerD protein needed for normal GR-dependent germination or of the SpoVAD protein likely involved in dipicolinic acid release early in germination. Loss of GerD also had no effect on levels of GRs or SpoVAD. Spores of a strain lacking the only B. subtilis prelipoprotein diacylglycerol transferase, GerF, also had no detectable GerD or the GerA's C subunit, both of which are most likely lipoproteins; GerA's A subunit was also absent. However, levels of GerB's C subunit, also almost certainly a lipoprotein, and GerK's A subunit were normal in gerF spores. These results with gerF spores were consistent with effects of loss of GerF on spore germination by different GRs.